Electrodiagnosis has a potential to identify neural damage in asymptomatic infants with closed spinal dysraphism - Park, Mina; Kim, Aram; Wang, Kyu-Chang; Lee, Ji Yeoun; Kim, Kyung Hyun; Kim, Joo Whan; Shin, Hyung-Ik (Child's nervous system, 2023)
Purpose The presence and progression of symptoms is the basis for deciding to perform surgery in infants with closed spinal dysraphism (CSD); however, identifying symptoms could be limited, making it difficult to decide. This study investigated whether an electrodiagnostic study (EDS) can provide evidence of neural damage in asymptomatic infants with CSD. Methods The study group comprised infants with CSD suspected of having neural damage based on structural abnormalities in spinal ultrasound findings. The patients’ medical records were reviewed retrospectively for their clinical presentation, neuroimaging findings, urodynamic study (UDS) results, EDS findings, and surgical status. Results Among 125 infants who underwent EDS and UDS, 117 (94%) had no clinical symptoms, except for cutaneous manifestations. Among these asymptomatic patients, 51 individuals (43.6%) had abnormal EDS findings; 33 subjects (28.2%) showed abnormal findings on EDS alone, while 37 (31.6%) on UDS alone, and 18 (15.4%) on both EDS and UDS. Chi-square test showed an opposite relationship between the two test results; when EDS was abnormal, UDS was often normal and vice versa ( χ 2 = 5.328, p = 0.021). In all cases with abnormal EDS, denervation potentials, such as fibrillation and positive sharp waves, were observed on needle electromyography. However, abnormal findings in the nerve conduction study were observed only in six cases. Conclusion Subclinical neural damage was identified through EDS in asymptomatic infants with CSD. EDS could be necessary to determine whether follow-up monitoring only or surgical intervention is required for this patient group complementing UDS findings.